Randomized Controlled Trial Comparing Daycare and Overnight Stay Laparoscopic Cholecystectomy - Salleh, AAM; Affirul, CA; Hairol, O; Zamri, Z; Azlanudin, A; Hilmi, MA; Razman, J (Soc Editrice Univ, 2024)
Background: This present study sought to review the feasibility and patients' satisfaction of laparoscopic cholecystectomy to be perform as daycare procedure. Materials and Methods. Sixty-two patients with symptomatic gallstones were recruited within a year. They were randomized into overnight stay and daycare groups. The outcomes and post-operative complications were analyzed. Results. Fifty-eight patients were eligible for analysis and four patients were excluded because of conversion to open cholecystectomy. All patients in daycare group reported no fever but two patients in the overnight stay group complaint of post-operative fever (p=0.150). The mean pain score using Visual Analogue Score (VAS) in daycare group was 2.93 but in the overnight stay was recorded as 3.59 (p=0.98). Five patients had post-operative nausea and vomiting (PONV) in daycare group compared to 2 patients in the overnight stay group (p=0.227). Patient's satisfaction were higher in the daycare group (p=0.160). All patients in daycare group were back at work within a week but in overnight stay, 11 patients had to stay off work for more than one week (p=0.01). Conclusion. Daycare laparoscopic cholecystectomy is safe and feasible. The satisfaction of daycare surgery is higher than overnight stay group. Patients' selection is an important aspect of its success.